2022
DOI: 10.1016/j.medcli.2021.07.012
|View full text |Cite
|
Sign up to set email alerts
|

The lung ultrasound “Rule of 7” in the prognosis of COVID-19 patients: Results from a prospective multicentric study

Abstract: Objetivo: Existe una evidencia creciente con respecto a los hallazgos de imagen de la enfermedad por coronavirus 2019 (COVID-19) en la ecografía pulmonar (LUS), sin embargo, aún no se ha explorado el uso de una herramienta combinada de pronóstico y triaje. El objetivo principal de este estudio fue determinar el impacto de la LUS en la predicción de la mortalidad de los pacientes con sospecha de afectación pulmonar por COVID-19. El objetivo secundario fue calcular una puntuación con los hallazgos del… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…The multicentre, prospective cohort study by Sun et al 27 in February to March 2020 recruited 402 patients in Wuhan, China, who presented to ED with COVID-19, had the LUS scores > 15/36 (12-region protocol) that predicted mortality, but may have been biased by including patients who were discharged. Conversely, two studies were similar to our eligibility criteria, the single-centre, prospective cohort study by de Alencar et al 9 from March to May 2020 demonstrated that 180 patients in Brazil, with the LUS scores > 18/36 (12-region protocol), and the multicentre, prospective cohort study by Tung-Chen et al 7 from March to September 2020 in Spain, with the LUS scores > 10, in combination with other markers, were both predictive of mortality.…”
Section: Discussionmentioning
confidence: 59%
“…The multicentre, prospective cohort study by Sun et al 27 in February to March 2020 recruited 402 patients in Wuhan, China, who presented to ED with COVID-19, had the LUS scores > 15/36 (12-region protocol) that predicted mortality, but may have been biased by including patients who were discharged. Conversely, two studies were similar to our eligibility criteria, the single-centre, prospective cohort study by de Alencar et al 9 from March to May 2020 demonstrated that 180 patients in Brazil, with the LUS scores > 18/36 (12-region protocol), and the multicentre, prospective cohort study by Tung-Chen et al 7 from March to September 2020 in Spain, with the LUS scores > 10, in combination with other markers, were both predictive of mortality.…”
Section: Discussionmentioning
confidence: 59%
“…In COVID‐19 diagnosis, a meta‐analysis pointed out that CT is sensitive and moderately specific while chest X‐ray is moderately sensitive and specific, and Ultrasound is sensitive but not specific, thus chest CT and ultrasound are more useful for ruling out COVID‐19 infection [3]. Several studies have discussed the use of one of the imaging scoring systems in prediction of COVID‐19's outcomes but no meta‐analysis had compared between them in predicting COVID's outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies and meta‐analyses have been done on the role of different imaging modalities such as X‐ray, computed tomography (CT), and ultrasound in COVID‐19 diagnosis. COVID 19 imaging findings have been reported in lots of studies; however, the use of a combined prognostic and triage tool has not been explored yet [3]. The prognostic importance of imaging modalities and their role in the risk stratification of patients already diagnosed with COVID‐19 have not yet been established.…”
Section: Introductionmentioning
confidence: 99%
“…Ultrasound ring-down artifacts called B-lines, or the ULC as defined in this study, have been described in COVID-19 and relate to prognosis. [3][4][5][6][7][8][9][10][11][12][13][14]19 ULC is highly sensitive for an abnormal interstitium 3,7 and can be present when radiographic findings are normal. 26,27 When found in the easily accessed lung anteroapical location, B-lines are unlikely to be due to gravity-dependent edema or aspiration and may be more specific for direct infection and the immune response, as the apices may be particularly prone to inhaled pathogens, formation of oxygen-free radicals, and poor lymphatic drainage.…”
Section: Discussionmentioning
confidence: 99%
“…1 Involvement of the lung has been the driving force for COVID-19 hospitalization and mortality 2 and can be easily detected by ultrasound. [3][4][5] Prior hospital-based point-of-care ultrasound studies of the lung have shown prevalence and prognostic value to the finding of B-lines, [6][7][8][9][10][11][12][13][14] a sign of interstitial edema, by using extensive bilateral lung imaging.…”
mentioning
confidence: 99%